Cultural Meanings of Lexicons Used in the Sudi Wadani Ritual in Tamblang Village - Ni Made Gita Pratiwi; I Gede Budasi; Made Aryawan Adijaya (Krinok:Jurnal Linguistik Budaya, 2026)
This research aims to identify the lexicon used in the Sudi Wadani ritual in Tamblang Village and analyze the cultural meanings embedded in it. The study was conducted in response to the decreasing understanding of ritual lexicons among the local community, particularly the younger generation, which may affect the preservation of the Balinese language and cultural identity. This study employed a descriptive qualitative method with an ethnolinguistic approach. The data were collected through non-participant observation and in-depth interviews with selected informants. The findings revealed that 25 lexicons were identified and classified into four categories: 10 lexicons of ritual stages, 4 of ritual tools, 6 of ritual participants, and 5 of ritual offerings. The identified lexicons reflect cultural values related to spiritual purification, devotion, harmony, religious identity, and the relationship between humans and Ida Sang Hyang Widhi. Therefore, documenting and understanding these ritual lexicons are essential for preserving the Balinese language, cultural heritage, and local identity, while also supporting the transmission of traditional knowledge to future generations.